Adhesion and characterization of the interface between aerospace standard primer and anodized aluminium alloy - Toh, Xin Hui (2015)
In aerospace industry, aluminum alloys have been the material of choice when it comes to building the fuselage, wing and supporting structure of modern passenger aircraft, military cargo and transport since 1930 [1]. Aluminum alloys are chosen due to their well-known performance characteristics, known fabrication costs, design experience, resistance to corrosion and high strength to weight ratio that will increase payload and save in fuel consumption. They usually undergo anodizing as a surface treatment to further enhance their protection against corrosion and to increase adhesion to paint. However, it has been understood that most paint adhesion problems are mainly due to delamination between the primer and the sealed anodic surface. Therefore, in this project, AA2024 specimens will be anodized under MIL-A-8625F Type II to understand the adhesion and characterization of the interface between the anodized aluminum alloy surface and two standard commercial aerospace primers A) with chromate, and B) chromate free. Three intrinsic factors have been designed to be taken into consideration for our experiments. They are the temperature used during the experiment, the presence of nickel incorporated in the sealing process and the presence of chromate in the primer. Two factors have been identified to be significant. The presence of nickel in the sealing process and chromate in the primer has shown to be more beneficial to adhesion. As such, it is vital to locate nickel further in the anodized oxide layer as the results from Scanning Electron Microscope (SEM) are not able to detect the nickel in the top sample surface as the total average over the surface is lower than 5 atomic percent.